FORMULATING ENGINEERING DEPARTMENT SERVICE LEADERSHIP FOR SUSTAINABILITY AND ENTREPRENEURSHIP IN FIVE-STAR HOTELS: A QUALITATIVE STUDY - Hamid, Uda Harris Abdul; Shalifullizam, Nur Ida Fatihah Che (INTERNATIONAL JOURNAL OF ENTREPRENEURSHIP AND MANAGEMENT PRACTISES (IJEMP), 2026)
The hospitality industry, particularly the five-star hotel sector, operates in a highly demanding environment that requires efficiency, sustainability and continuous innovation. Within this context, the Engineering Department plays a critical role in ensuring operational continuity through the management of technical systems, maintenance and resource optimisation. However, leadership in this department has traditionally been dominated by technical and operational orientations, with limited emphasis on service-oriented leadership. This study aims to conceptualise Engineering Department Service Leadership and examine its role in supporting sustainability and entrepreneurial practices in five-star hotels. A qualitative approach using Basic Qualitative Inquiry was employed. Data were collected through semi-structured interviews with five participants, comprising Engineering Managers and Hotel Managers. The data were analysed using manual coding and thematic analysis. The findings indicate that although technical leadership remains dominant, service leadership elements—such as employee support, effective communication and empowerment—play a crucial role in enhancing sustainability initiatives and operational innovation. This study contributes to the development of a conceptual understanding of service-oriented leadership within hotel engineering departments and provides a foundation for a more holistic leadership model aligned with sustainability and entrepreneurial goals in the luxury hospitality sector.